2018
DOI: 10.1111/apt.14834
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous rather than intravenous ustekinumab induction is associated with comparable circulating drug levels and early clinical response: a pilot study

Abstract: Ustekinumab trough concentrations are comparable whether ustekinumab induction treatment was administered subcutaneously or intravenously. A significant improvement in symptoms and faecal calprotectin was noted. These results support the use of subcutaneous induction as an alternative if there are barriers to intravenous induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…10 The trough levels we observed at Week 8 did not show correlation with clinical outcomes, in contrast with the findings of others. 25,26 This may be for two possible reasons: First, trough levels were performed in our study in a subgroup of 82 patients, which may impact the statistical power. Second, in Battat et al's and Adedokun et al's studies, UST trough levels were better correlated to objective end points such as CRP or endoscopy than clinical end points.…”
Section: Discussionmentioning
confidence: 99%
“…10 The trough levels we observed at Week 8 did not show correlation with clinical outcomes, in contrast with the findings of others. 25,26 This may be for two possible reasons: First, trough levels were performed in our study in a subgroup of 82 patients, which may impact the statistical power. Second, in Battat et al's and Adedokun et al's studies, UST trough levels were better correlated to objective end points such as CRP or endoscopy than clinical end points.…”
Section: Discussionmentioning
confidence: 99%
“…The total study population was of 4,487 patients. The majority of the included studies was observational cohort studies with 2,260 patients, 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 and 4 of the included studies were RCTs with 2,227 patients. 13 17 50 51 We have presented data on age, gender, location of CD disease, disease phenotype, route of administration, and drug dose.…”
Section: Methodsmentioning
confidence: 99%
“…Only one study showed good quality. 40 Fifteen studies were rated to have fair quality, 23 24 26 27 29 31 34 35 37 38 39 41 42 44 47 and the remaining 10 trials were of poor quality. 25 28 30 32 33 36 43 46 48 49…”
Section: Methodsmentioning
confidence: 99%
“…4 For ustekinumab, a pilot study recently evaluated induction therapy with the SC (rather than IV) formulation in patients with CD, establishing comparability of PK and acceptability of the approach. 136 …”
Section: Delivering the Benefits Of Innovative Biologics To Patientsmentioning
confidence: 99%